Shiny broken pieces - Charaipotra, Sona; Clayton, Dhonielle (New York, NY : HarperTeen, an imprint of HarperCollins Publishers, 2016)
June is starting to finally see herself as a prima ballerina. However, getting what she wants might cost her everything--including the only boy she's ever loved. Legacy dancer Bette is determined to clear her name after she was suspended and accused of hurting her rival, Gigi. Even if she returns, though, will she ever regain the spotlight she craves? And Gigi is not going to let Bette--or the other dancers who bullied her--go unpunished. But as revenge consumes her, Gigi may be the one who pays the price.
Keywords: Ballerinas -- Juvenile fiction; Competition (Psychology) in adolescence -- Juvenile fiction; Teenage girls -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Dance and race -- Juvenile fiction; Manhattan (New York, N.Y.) -- Fiction; Young adult fiction